First-year seminars through the lens of Vincent Tinto's theories of student departure. A systematic review - Samoila, Magda Elena; Vrabie, Tina (Frontiers in Education, 2023)
Vincent Tinto is a towering figure in the study of dropout in higher education whose theory regarding student departure is a widely accepted contribution that explains how students become involved in the academic community and how their level of engagement impacts their decision to persist or to drop out. The aim of this study is to advance understanding of how Vincent Tinto’s theories influence the current practices and support services offered by higher education institutions to freshman students through first-year seminars (FYS). A systematic review was conducted based on 23 peer-reviewed articles published between 2020 and 2022, selected through a multi-stage process. The findings indicate three categories of studies that capitalize on Tinto’s theories with regard to the design, conduct and evaluation of first-year seminars: a. studies that assess the role of students’ personal and psychological variables, considered within FYS; b. studies that analyze the pedagogical and counselling interventions destined to students within FYS; c. studies that analyze the role of the social and relational dimension within FYS.